2011
DOI: 10.1103/physrevc.83.024314
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation properties of the strength function associated with the giant quadrupole resonance inPb208

Abstract: We performed fluctuation analysis by means of the local scaling dimension for the strength function of the isoscalar (IS) giant quadrupole resonance (GQR) in 208 Pb where the strength function is obtained by the shell model calculation including 1p1h and 2p2h configurations. It is found that at almost all energy scales, fluctuation of the strength function obeys the Gaussian orthogonal ensemble (GOE) random matrix theory limit. This is contrasted with the results for the GQR in 40 Ca, where at the intermediate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Recent work by Aiba et al [49], published after submission of our manuscript, circumstantiates our conclusions based on an extraction of the local scaling dimension of fine structure fluctuations in shell-model calculations of the 40 Ca GQR strength function.…”
Section: Acknowledgementssupporting
confidence: 74%
“…Recent work by Aiba et al [49], published after submission of our manuscript, circumstantiates our conclusions based on an extraction of the local scaling dimension of fine structure fluctuations in shell-model calculations of the 40 Ca GQR strength function.…”
Section: Acknowledgementssupporting
confidence: 74%
“…It could be shown that in this case the spreading width dominates over the escape width but the deduced scales depended strongly on the assumptions about the (unknown) number of doorway states. Later, new methods were proposed for the extraction of such scales based an a local scaling dimension approach [17,18,19], an entropy index method [20,21], and the use of wavelet techniques [22,23]. A comprehensive discussion of the advantages and limitations of the various methods concluded that wavelet analysis is most promising [24].…”
Section: Introductionmentioning
confidence: 99%
“…Various measures have been proposed in the past, viz. averaging of spectra at various scales [5], Fourier analysis [20], correlation analysis [21], the entropy index method [22,23], local scaling dimension [24,25], and wavelet analysis [26]. We have chosen wavelet analysis as it offers a quantification of the energy scales of fine structures while resolving the strength of fine structures in both excitation energy and energy scale.…”
Section: Introductionmentioning
confidence: 99%